Experimental adaptation to singular pathogen challenge reduces susceptibility to novel pathogens in Drosophila melanogaster - Aparajita Singh; Aabeer Basu; Biswajit Shit; Tejashwini Hegde; Nitin Bansal; Nagaraj Guru Prasad (Current Research in Insect Science)
Hosts often encounter and must respond to novel pathogens in the wild, that is pathogens that they have not encountered in recent evolutionary history, and therefore are not adapted to. How hosts respond to these novel pathogens and the outcome of such infections can be shaped by the host's evolutionary history, especially by how well adapted the host is to its native pathogens, that is pathogens they have evolved with. Host adaptation to one pathogen can either increase its susceptibility to a novel pathogen, due to specialization of immune defenses and trade-offs between different arms of the immune system, or can decrease susceptibility to novel pathogens by virtue of cross-resistance. Using laboratory Drosophila melanogaster populations, we explore if hosts experimentally adapted to surviving infection challenges by a single bacterial pathogen are also better at surviving infection challenges by novel bacterial pathogens. We found that such hosts can survive infection challenges by multiple novel pathogens, with the expanse of cross-resistance determined by the identity of the native pathogen and sex of the host. Therefore, we have demonstrated that cross-resistance can evolve in host populations by virtue of adaptation to a single pathogen. This observation has important ecological consequences, especially in the modern era where spillover of novel pathogens is a common occurrence due to various factors, including climate change.